A comparison on microstructure and mechanical properties of electric discharge metal matrix nickel and silica composite coating on duplex stainless steel. (February 2021) - Arun, Ilangovan; Yuvaraj, C; Madhu, A; Ramesh, T
Electric Discharge Alloying/Coating a thermal process of elemental deposition together with pyrolysis carbon enhance various properties. Nickel and silica both provide excellent property, but the solidification rate differs the material microstructural properties (amorphous) that improves its properties under diverse working conditions. In present study analysis of properties such as surface roughness, Microstructure, layer thickness, elemental composition, porosity, decarburizing depth is detailed through metallurgical characterizations and mechanical testing are compared to nickel and silica. Nickel holds a hardness value of 1272 HV and across 968 HV with minimal in carter, pokes, splatters having uniform boundaries that improves friction co-efficient, limiting wear resistant, phase transformation, oxidation, and graphite flakes confirm self-lubrication properties at room temperature under higher loading condition. Silica having 1284 HV on the surface and across it reaches to 980 HV due to dispersed elements and its phase transformation of silica to silica carbide directs secondary arching improves bonding by restrictive carbon deposition promotes passage to speak. This limits the porosity, coating layer thickness and increases metal matrix composition in decarburizing layer holds stability towards coating. Nickel affords surface properties limiting matrix composite, oxidation, and grain growth where else silica provides exceptional in metallurgical mixed composition improves the mechanical behaviour of coating.